2011
DOI: 10.1302/0301-620x.93b9.26436
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the quality of total hip replacement in a tertiary care department using a cumulative summation statistical method (CUSUM)

Abstract: The purpose of this study was to define immediate post-operative 'quality' in total hip replacements and to study prospectively the occurrence of failure based on these definitions of quality. The evaluation and assessment of failure were based on ten radiological and clinical criteria. The cumulative summation (CUSUM) test was used to study 200 procedures over a one-year period. Technical criteria defined failure in 17 cases (8.5%), those related to the femoral component in nine (4.5%), the acetabular compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Another study monitoring the quality of THR found that approximately 25% of all THRs failed due to factors related to technical errors (Biau et al. 2011 ). The types of injury and their frequencies found in the present study were also very similar to those reported earlier for closed malpractice claims of THR recipients in the USA (Matsen et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study monitoring the quality of THR found that approximately 25% of all THRs failed due to factors related to technical errors (Biau et al. 2011 ). The types of injury and their frequencies found in the present study were also very similar to those reported earlier for closed malpractice claims of THR recipients in the USA (Matsen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Acetabular-side errors have previously been shown to account for half of all technical errors in THRs (Biau et al. 2009 , 2011 ), and up to 60% of acetabular components have been shown to be in a suboptimal position, depending on the target ranges used (Barrack et al. 2013 , Lee et al.…”
Section: Discussionmentioning
confidence: 99%
“…Patients, doctors, and public health authorities are using these methods to detect and, if necessary, correct inadequate performance [6,9,10,23,24]. The use of these methods such as the cumulative summation (CUSUM) test [17] has been proposed in various surgical and interventional specialties [2,5,11,15,18]. This control chart is designed to detect the deviation from target of some characteristic of a product.…”
Section: Introductionmentioning
confidence: 99%
“…This control chart is designed to detect the deviation from target of some characteristic of a product. For instance, it may be used to detect an increase in the postoperative infection rate or in the proportion of THAs that fails to meet some prespecified standards [2]. These methods provide ongoing feedback to physicians learning a technique [18], using new implants [2], or simply attempting to reach some target level of technical competence [6,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation